Bedside Handover untuk Meningkatkan Kepuasan Perawat dalam Memberikan Asuhan Keperawatan - Rovina Efranti Br Barus; Rika Endah Nurhidayah; Jenny Marlindawani Purba (FORIKES, 2024)
The handover process in the inpatient ward of Efarina Etaham Berastagi Hospital is still carried out traditionally at the nurse station without direct involvement of patients and families at the patient's bedside. Therefore, a study is needed that aims to analyze the effectiveness of bedside handover to improve nurse satisfaction in providing nursing care to patients. The design of this study was nonequivalent control group pretest-posttest. This study involved 64 nurses at Efarina Etaham Berastagi Hospital who were selected using the total population sampling technique. The treatment group carried out bedside handover, while the control group carried out handover at the nurse station. In the pre- and post-intervention phases, nurse satisfaction levels were measured using a questionnaire. The difference in satisfaction levels between before and after the intervention was analyzed using the Wilcoxon test, and this was carried out in each group. The results showed that for the treatment group, the p-value was 0.000, so it was interpreted that there was a change in nurse satisfaction after bedside handover. Meanwhile, for the control group, the p-value was 0.082, so it was interpreted that there was no change in nurse satisfaction after handover at the nurse station. Furthermore, it was concluded that bedside handover was effective in increasing nurse satisfaction in providing nursing care to patients.Keywords: bedside handover; nursing care; patients; nurse satisfaction ABSTRAK Proses handover di ruang rawat inap RS Efarina Etaham Berastagi masih dilaksanakan secara tradisional di nurse station tanpa keterlibatan pasien dan keluarga secara langsung di samping bed pasien. Oleh karena itu diperlukan penelitian yang bertujuan untuk menganalisis efektifitas bedside handover untuk meningkatkan kepuasan perawat dalam memberikan asuhan keperawatan kepada pasien. Rancangan penelitian ini adalah noneqivalent control group pretest-posttest. Penelitian ini melibatkan 64 perawat di RS Efarina Etaham Berastagi yang dipilih dengan teknik total population sampling. Kelompok perlakuan menjalankan bedside handover, sedangkan kelompok kontrol menjalankan handover di nurse station. Pada fase sebelum dan sesudah intervensi dilakukan pengukuran tingkat kepuasan perawat menggunakan kuesioner. Perbedaan tingkat kepuasan antara sebelum dan sesudah intervensi dianalisis dengan uji Wilcoxon, dan ini dilakukan pada masing-masing kelompok. Hasil penelitian menunjukkan bahwa untuk kelompok perlakuan, nilai p adalah 0,000, sehingga ditafsirkan bahwa ada perubahan kepuasan perawat setelah dilakukan bedside handover. Sementara itu, untuk kelompok kontrol, nilai p adalah 0,082, sehingga ditafsirkan bahwa tak ada perubahan kepuasan perawat setelah dilakukan handover di nurse station. Selanjutnya disimpulkan bahwa bedside handover efektif untuk meningkatkan kepuasan perawat dalam memberikan asuhan keperawatan kepada pasien.Kata kunci: bedside handover; asuhan keperawatan; pasien; kepuasan perawat